2018
DOI: 10.2147/dnnd.s170771
|View full text |Cite
|
Sign up to set email alerts
|

Continuous noninvasive ventilation for respiratory failure in patients with amyotrophic lateral sclerosis: current perspectives

Abstract: Respiratory failure is a recognized late complication of amyotrophic lateral sclerosis. It is related to the neurological progression of the diseases with the impairment of the respiratory musculature. Survival and quality of life of amyotrophic lateral sclerosis patients is improved by using noninvasive mechanical ventilation. The rate of long-term mechanical ventilation is different within and between countries. Cultural factors, socioeconomic conditions, and physician attitude often influence the decision t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 60 publications
(68 reference statements)
0
9
0
Order By: Relevance
“…Usually, ALS leads to death within 3–5 years [ 1 , 2 ]. Respiratory failure is recognized as one of the main complications of ALS and one of the main causes leading to death [ 4 , 5 ]. The appearance of respiratory failure is caused by the impairment of the respiratory musculature, and it is influenced by the concomitant presence of other respiratory pathologies [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Usually, ALS leads to death within 3–5 years [ 1 , 2 ]. Respiratory failure is recognized as one of the main complications of ALS and one of the main causes leading to death [ 4 , 5 ]. The appearance of respiratory failure is caused by the impairment of the respiratory musculature, and it is influenced by the concomitant presence of other respiratory pathologies [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Respiratory failure is recognized as one of the main complications of ALS and one of the main causes leading to death [ 4 , 5 ]. The appearance of respiratory failure is caused by the impairment of the respiratory musculature, and it is influenced by the concomitant presence of other respiratory pathologies [ 4 , 5 ]. The loss of function of the phrenic nerve induces diaphragm weakness, leading as a consequence to dyspnea, orthopnea, and hypoventilation [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, noninvasive ventilation may fail due to poor adherence. Although NIV should be performed for an adequate number of hours, many studies have shown suboptimal adherence in a non-negligible percentage of cases [ 54 , 55 ]. The main causes of poor adherence are: interface-related discomfort; unintentional leaks; patient–ventilator asynchrony; patient reluctance; lack of support from the family; absent or delayed follow-up by the healthcare team; absence of symptom improvement; lack of knowledge of therapeutic goals; psychological issues; and low socioeconomic status [ 56 , 57 ].…”
Section: The Burden Of Respiratory Treatmentsmentioning
confidence: 99%
“…Non-invasive Ventilation Support-Settings (NVS) are often needed initially at night in patients with neuromuscular disease. However, when the condition worsens, it becomes necessary even during the day [1][2][3]. Facial masks (nasal, oronasal, nasal pillows, and mouthpieces) are the most used to convey NVS [1].…”
Section: Introductionmentioning
confidence: 99%